2017
DOI: 10.1021/acs.jpca.7b04771
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies on the Kinetics of Multi-Channel Gas-Phase Unimolecular Decomposition of Acetaldehyde

Abstract: Theoretical kinetic studies are performed on the multichannel thermal decomposition of acetaldehyde. The geometries of the stationary points on the potential energy surface of the reaction are optimized at the MP2(full)/6-311++G(2d,2p) level of theory. More accurate energies are obtained by single point energy calculations at the CCSD(T,full)/augh-cc-pVTZ+2df, CBS-Q and G4 levels of theory. Here, by application of steady-state approximation to the thermally activated species CHCHO* and CHCHOH* and performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 49 publications
3
13
0
Order By: Relevance
“…A recent theoretical study on the multichannel thermal decomposition of acetaldehyde by our research group has revealed that the CH 3 CHO ⇄ CH 2 CHOH process is indeed an important process. 19 To date, all experimental and theoretical studies on the elementary unimolecular decomposition of acetone are concentrated on its dissociation to CH 3 CO + CH 3 . As mentioned above, recent experimental studies on CH 3 COCH 3 and a similar molecule, CH 3 CHO, reveal that other reaction paths could be of importance in the kinetics of the unimolecular reaction of acetone.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent theoretical study on the multichannel thermal decomposition of acetaldehyde by our research group has revealed that the CH 3 CHO ⇄ CH 2 CHOH process is indeed an important process. 19 To date, all experimental and theoretical studies on the elementary unimolecular decomposition of acetone are concentrated on its dissociation to CH 3 CO + CH 3 . As mentioned above, recent experimental studies on CH 3 COCH 3 and a similar molecule, CH 3 CHO, reveal that other reaction paths could be of importance in the kinetics of the unimolecular reaction of acetone.…”
Section: ■ Introductionmentioning
confidence: 99%
“…44,45 The computed effective reduced masses and energies along the hindered internal rotations are fitted by Fourier series, and their corresponding sums of states are included in total sum of states. 19 The above-mentioned theory is just applicable for estimating the sum of states of a tight transition state. As will be shown in the next sections, two distinct channels of bond breaking are considered in the acetone decomposition, leading to products sets of CH 3 + CH 3 CO and H + CH 3 COCH 2 .…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1–8 ] In acetaldehyde pyrolysis and photolysis, it has been shown that the CH 3 radical production is probable, specifically in the high‐temperature regime caused by the combustion processes. [ 9–12 ] These super‐reactive radicals can play a significant role in the fate of acetaldehyde molecules as chain carriers and can react either with acetaldehyde itself or with other species produced.…”
Section: Introductionmentioning
confidence: 99%
“…Acetaldehyde, recognized as an intermediate in oxygenated fuel combustion, [ 31,32 ] and its decomposition process have received some theoretical interests within recent years. [ 11,12,33 ] Interestingly, almost none of them has reported a comprehensive theoretical work on an important secondary reaction like CH 3 CHO + CH 3 . This lack of knowledge on the reaction CH 3 CHO + CH 3 in the literature drew our attention to explore the mechanism and kinetics of this reaction.…”
Section: Introductionmentioning
confidence: 99%